Minor intron retention drives clonal hematopoietic disorders and diverse cancer predisposition - Inoue, Daichi; Polaski, Jacob T.; Taylor, Justin; Castel, Pau; Chen, Sisi; Kobayashi, Susumu; Hogg, Simon J.; Hayashi, Yasutaka; Pineda, Jose Mario Bello; El Marabti, Ettaib; Erickson, Caroline; Knorr, Katherine; et al. (Nature genetics, 2021)
Most eukaryotes harbor two distinct pre-mRNA splicing machineries: the major spliceosome, which removes >99% of introns, and the minor spliceosome, which removes rare, evolutionarily conserved introns. Although hypothesized to serve important regulatory functions, physiologic roles of the minor spliceosome are not well understood. For example, the minor spliceosome component ZRSR2 is subject to recurrent, leukemia-associated mutations, yet functional connections among minor introns, hematopoiesis and cancers are unclear. Here, we identify that impaired minor intron excision via ZRSR2 loss enhances hematopoietic stem cell self-renewal. CRISPR screens mimicking nonsense-mediated decay of minor intron-containing mRNA species converged on LZTR1, a regulator of RAS-related GTPases. LZTR1 minor intron retention was also discovered in the RASopathy Noonan syndrome, due to intronic mutations disrupting splicing and diverse solid tumors. These data uncover minor intron recognition as a regulator of hematopoiesis, noncoding mutations within minor introns as potential cancer drivers and links among ZRSR2 mutations, LZTR1 regulation and leukemias. Loss of function of the minor spliceosome component ZRSR2 enhances hematopoietic stem cell self-renewal through minor intron retention of its target LZTR1, which is a regulator of RAS-related GTPases. Minor intron retention of LZTR1 was also identified in Noonan syndrome and diverse solid tumor types.